Pendampingan Akuntansi Koperasi pada Koperasi Konsumen KopWil 7 di Surabaya - Hwihanus Hwihanus; Dyah Rini Prihastuty; Sri Rahayuningsih; Achmad Sofyan; Suhaima Rafia Mansyur (Lembaga Pengembangan Kinerja Dosen, 2026)
Cooperatives play a strategic role in improving the welfare of their members through business management based on the principles of family and economic democracy. However, many cooperatives still face obstacles in implementing accounting, particularly in recording transactions and preparing systematic financial reports, including the Consumer Cooperative of KopWil 7 in Surabaya. This is due to the limited understanding of cooperative accounting by the management and the suboptimal financial recording and reporting system. This community service activity aims to improve the competence of cooperative management and members in financial management through training and mentoring on cooperative accounting. The implementation method uses a participatory approach that includes needs identification, training, report preparation assistance, and evaluation of training and mentoring. The material provided covers basic cooperative accounting concepts, recording financial transactions, cash management, and preparing simple financial reports. The results of the activity showed an increase in participants' understanding of cooperative accounting principles, their ability to systematically record transactions, and their skills in preparing simple financial reports. In addition, the management began implementing a more structured recording system so that financial information becomes more transparent and accountable. This activity makes a positive contribution to improving cooperative financial governance, supporting more appropriate decision-making, and strengthening the sustainability of cooperative businesses. Therefore, cooperative accounting training and mentoring can be an effective strategy in increasing the financial management capacity and accountability of cooperative organizations.